Review of clinical profile and bacterial spectrum and sensitivity patterns of pathogens in febrile neutropenic patients in hematological malignancies: A retrospective analysis from a single center - Arun B Karanwal; Bharat J Parikh; Parijat Goswami; Harsha P Panchal; Bhavesh B Parekh; Kaushal B Patel (Indian Journal of Medical and Paediatric Oncology)
Background: The aim of this study was to study clinical profile with bacterial spectrum and susceptibility patterns of pathogens in culture positive febrile neutropenic (FN) patients of hematological malignancies. Materials and Methods: We retrospectively reviewed the medical records of 23 hematological malignancy patients admitted with chemotherapy induced febrile neutropenia with culture positive results, at our institute between June 2011 and December 2011. Results: A total of 23 patients were studied 12 males and 11 females, with a median age of 35 years. Most common diagnosis was acute leukemia (78%) with the majority of patients developing febrile neutropenia during the induction phase of treatment. Most common presenting symptoms were fever, cough, dyspnea, and diarrhea. Primary site of infection was not found in 47% of patients while the rest had lung, gastro-intestinal and skin/soft-tissue infection. Overall 23 organisms were isolated during the study period, from blood (56%), sputum (46%), stool (23%), and nasal swab from one patient. Gram negative bacteria accounted for 78% of organisms while gram positive organisms accounted for 22% of the total isolates. The most common organisms were: Escherichia coli (43%), Staphylococcus aureus (22%), Pseudomonas aeruginosa (17.4%) and Klebsiella pneumonia (17.4%). Antibiotic sensitivity patterns of these bacteria were studied. Gram negative bacterial infections were associated with higher mortality (89%). Conclusions: Induction phase of treatment in acute leukemia is the major cause of FN in hematological malignancies at our institute and gram negative organisms are the predominant organisms with E. coli as major isolate while S. aureus represents the most common gram positive organism. Amikacin and cefoperazone/sulbactum appears to be initial antibiotic appropriate to cover most gram negative pathogens while vancomycin to be added for suspected gram positive infections. FN represents a major cause of morbidity and mortality in hematological malignancy patients, high index of suspicion and early empirical antibiotics with supportive care are main interventions to reduce high mortality for these patients. Antibiotics should be modified according to culture sensitive report as soon as possible.